Fitness profiles of elite Portuguese Rugby Union players - Vaz, L.; Morais, T.; Rocha, H.; James, N. (Journal of Human Kinetics, 2014)
The aim of this study was to describe the fitness profiles of senior elite Portuguese rugby players. Forty-six senior Portuguese rugby players, classified as backs (n=22; age 26.2±2.8) and forwards (n=24; age 26.7±2.9) were assessed during physical testing sessions carried out for the Portuguese National rugby team. The body composition, maximum strength and anaerobic capacity of players are hypothesized to be important physical characteristics as successful performance in rugby is predicated on the ability to undertake skilled behaviours both quickly and whilst withstanding large forces when in contact situations. No absolute differences were found between the backs and forwards for the speed performance variables although positional differences were found across all speeds when assessed relative to body mass since the forwards were significantly heavier. Coaches and the management team can use this information for monitoring progressive improvements in the physiological capacities of rugby players. These physical characteristics of elite rugby players provide normative profiles for specific positions and should form the basis of developmental programmes for adolescents.